2020
DOI: 10.1039/d0cp01835j
|View full text |Cite
|
Sign up to set email alerts
|

Highly-excited state properties of cumulenone chlorides in the vacuum-ultraviolet

Abstract: A detailed understanding of VUV-driven photochemistry in complex organic molecules is challenging. This quantum chemical analysis reports the electronic properties and ionization energies up to the VUV range (6–11 eV) of the chlorinated cumulenones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…17−19 Recent work has also shown that the reference geometry has little effect on the excitation energy, implying that the starting geometry will have no qualitative or meaningful quantitative effects on the implications of this work. 20 All quantum-chemical computations make use of the MOLPRO 2020.1 program. 21,22 The UV spectral features in question can be modeled only as convolved spectra since several computed excitations add together to create the experimentally correlative features.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17−19 Recent work has also shown that the reference geometry has little effect on the excitation energy, implying that the starting geometry will have no qualitative or meaningful quantitative effects on the implications of this work. 20 All quantum-chemical computations make use of the MOLPRO 2020.1 program. 21,22 The UV spectral features in question can be modeled only as convolved spectra since several computed excitations add together to create the experimentally correlative features.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…For those structures that require new optimizations (such as nonminimum dimers), second-order Møller–Plesset perturbation theory (MP2) with the aug-cc-pVDZ basis set is used. Once the reference geometry is selected, the dihedral angles (θ) as defined for each explored system are displaced by 3.0° intervals, creating constrained scans. From each of these θ displacments, equation-of-motion coupled cluster theory at the singles and doubles levels (EOM-CCSD) with an aug-cc-pVTZ basis set is used to compute the vertical electronically excited states with transition energies of less than 8.0 eV. Recent work has also shown that the reference geometry has little effect on the excitation energy, implying that the starting geometry will have no qualitative or meaningful quantitative effects on the implications of this work . All quantum-chemical computations make use of the MOLPRO 2020.1 program. , …”
Section: Methodsmentioning
confidence: 99%
“…those with more than a dozen atoms. [74][75][76][77][78] Geometry optimizations of the benchmark dyes utilize B3LYP/6-311G(d,p) within Gaussian09 and Gaussian16. 79,80 The geometry optimizations provide the molecular structures for the subsequent TD-DFT 31 excited state computations producing the approximate l max (i.e.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The excitation energies change by less than 0.005 eV in all instances in line with previous work. 77 3.2.2 Orbital energies. Fig.…”
Section: Benchmark Molecule Analysismentioning
confidence: 99%